(untitled) (Journal of Nematode Morphology and Systematics, 2012)
Systematic position of six genera, namely Paraxonchium Krall, 1958, Gopalus Khan, Jairajpuri & Ahmad, 1987, Tendinema Siddiqi, 1995, Parapalus Loof & Zullini, 2000, Cerviconema Andrassy, 2009 and Ramphidorylaimus gen. n., of the family Paraxonchiidae Dhanachand & Jairajpuri, 1981, is discussed. These genera are differentiated mainly on the basis of their odontostyle morphology. Paraxonchium has odontostyle mostly asymmetrical, dorsally bent and with a large aperture. Ramphidorylaimus gen. n. is characterized by having a significantly narrower odontostyle, somewhat beak-shaped, with a small aperture, and often with its dorsal and ventral arms ending almost at same level. Gopalus has long, attenuated and straight odontostyle with a small aperture; and cardiac glands poorly developed. Tendinema is distinguishable in having small, symmetrical odontostyle, pars refringens vaginae absent, and males with just one or two ventromedian supplements. Parapalus has long, slender and symmetrical odontostyle. Cerviconema is characterized by its offset lip region, small symmetrical odontostyle with a small aperture, cardiac glands present, and pars refringens vaginae well developed. Ramphidorylaimus ramphionus (Jairajpuri, 1966) comb. n., R. macrodontus (Hodda, Bloemers, Wanless & Siddiqi, 1994) comb. n., R. loofi (Hodda, Bloemers, Wanless & Siddiqi, 1994) comb. n. and Paraxonchium laetificans Andrassy, 1956, are re-described based on the study of fresh material and/or paratypes. Lists of species under each genus and keys for their identification have been provided.